Orthodontic Treatment of Bilateral Transposition of Maxillary Canines and Lateral Incisors - Mandla Dominic Nyakale (Hindawi Limited, 2022)
Dental transposition is a severe disturbance of tooth position and its eruptive sequence. It may affect any tooth, and it may occur at any location within the dental arch, although some teeth may be more frequently affected than others. There are several types of dental transposition, and their classification depends on the type of teeth involved. The aetiology of transposition is not very clear and has always been the subject of controversies, and it is still not completely understood. The prevalence of dental transposition and the factors related to this dental anomaly have been well documented in the literature. When treating dental transposition, many factors which may affect the treatment results must be considered, such as aesthetics, occlusion, treatment duration, patient comfort, patient cooperation, and periodontal support. Various treatment options are currently available for the treatment of dental transposition. Successful treatment outcomes depend on the patient's age, concern about facial and dental aesthetics, motivation of the patient, functional requirements, type of malocclusion, and the position of the root apices. The present case report is aimed at outlining the orthodontic treatment of a young adult patient diagnosed with bilateral maxillary canine-lateral incisor transposition.